PEMANFAATAN APLIKASI QUIZIZZ DALAM PENGEMBANGAN SOAL SHOROF BERBASIS KEMAMPUAN BERPIKIR KREATIF - Nurul Amaliya; Wasilah; Jamanuddin (Universitas Islam Negeri Palopo, 2026)
Shorof learning, as a fundamental aspect of Arabic language mastery, is often perceived as difficult by high school students, particularly when assessment relies on conventional methods that inadequately stimulate creative thinking skills. This study aims to examine the effectiveness of using the Quizizz application in developing shorof test items based on creative thinking skills as an interactive and innovative assessment alternative. This study employed a Research and Development (R&D) method using the Borg and Gall model, simplified into six stages: needs analysis, design, development, validation, revision, and try-out, involving grade XI students of SMA Azharyah Palembang. The validation results indicate that the product is highly feasible, with scores of 90% from material experts and 93% from media experts. The results show that Quizizz-based shorof assessment is effective in improving student learning outcomes, as evidenced by the experimental class post-test mean of 74.42 compared to the control class mean of 53.28, with an N-Gain Score of 57.66% (moderate category). The independent sample t-test confirms a significance value of < 0.05, indicating a statistically significant difference between the two groups. These findings suggest that integrating Quizizz into shorof assessment creates a more interactive, engaging, and student-centered evaluation process. Future research is recommended to extend digital assessment to other Arabic language topics and examine its long-term impact on language competence. Pembelajaran shorof sebagai salah satu aspek penting dalam penguasaan bahasa Arab masih sering dianggap sulit oleh siswa SMA, terutama ketika evaluasi hanya menggunakan metode konvensional yang kurang menstimulasi kemampuan berpikir kreatif. Penelitian ini bertujuan untuk menguji efektivitas penggunaan aplikasi Quizizz dalam pengembangan soal shorof berbasis kemampuan berpikir kreatif sebagai alternatif evaluasi yang lebih interaktif dan inovatif. Penelitian ini menggunakan metode Research and Development (R&D) dengan model Borg and Gall yang disederhanakan menjadi enam tahap, meliputi analisis kebutuhan, perancangan, pengembangan, validasi, revisi, dan uji coba pada siswa kelas XI SMA Azharyah Palembang. Hasil validasi menunjukkan bahwa produk sangat layak digunakan dengan skor 90% dari ahli materi dan 93% dari ahli media. Hasil penelitian menunjukkan bahwa penggunaan Quizizz efektif dalam meningkatkan hasil belajar siswa, yang dibuktikan dengan nilai post-test kelas eksperimen sebesar 74,42 dibandingkan kelas kontrol sebesar 53,28, dengan N-Gain Score sebesar 57,66% (kategori sedang). Uji independent sample t-test juga menunjukkan nilai signifikansi < 0,05, yang menandakan adanya perbedaan yang bermakna antara kedua kelompok. Temuan ini menunjukkan bahwa integrasi Quizizz dalam evaluasi shorof mampu menciptakan proses penilaian yang lebih interaktif, menyenangkan, dan sesuai dengan karakteristik belajar siswa masa kini